MTC: Visualization method of assessing physical movements with dribbling performance of basketball based in 3D Space - Liu, Mengru; Lau, Newman; Tang, Kelly (Journal of Graphic Engineering and Design, 2023)
We present a basketball training visualization method – Motion Time Cylinder (MTC) designed to help novice players learn basketball techniques more easily. The basketball player can select their preferred movement to learn and visualize the body and joint movements in detail. Extensive visualization as a graphical assistant help supports the player in understanding 3D movements from the visual patterns. At the same time, players can understand the coordination and spatial relationship when playing the movement. The visualization principle is based on the mapping of body movement into the graphic of clock-based division locations. The movements can then be represented by the translation pattern between the frontal and transverse planes of cylinder spaces. As a result, the movement can be visualized by rendering the translation pattern base on the clock from a specific perspective, for example, an orthogonal view. This paper explains the visualization principles of the mapping and pattern as well as the graphical representation based on user perception. Article history: Received (May 27, 2022); Revised (November 3, 2022); Accepted (November 9, 2022); Published online (June 1, 2023)